2021
DOI: 10.1149/1945-7111/ac0459
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive Non-Enzymatic Urea Sensor Based on Ni(OH)2/Mn3O4/rGO/PANi Nanocomposites Using Screen-Printed Electrodes

Abstract: Herein, we have developed a highly sensitive non-enzymatic biosensor for the detection of the urea using nickel-manganese oxo/hydroxo metal nanoparticles on reduced graphene oxide, and these nanocomposites were made using the hydrothermal reduction method. Then, the characteristics of these nanocomposites were examined using Fourier transform infrared spectroscopy (FT-IR spectroscopy), energy-dispersive X-ray spectroscopy (EDX), scanning electron microscopy (SEM), inductive coupled plasma (ICP), XRD surface ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A regression coefficient of 0.99 indicates the NiCo 2 O 4 nanomaterial could play a role in the quantification of urea from practical samples. In Table 1 [ 36 , 37 , 38 , 39 , 40 , 41 ], the proposed non-enzymatic urea sensor configuration is found to perform better than or as well as many of the recently published urea sensors/biosensors in terms of wide linear range, especially for the non-enzymatic urea sensors. The LOD of the presented is also superior to many of the reported works’ enzymatic and non-enzymatic sensors, as given in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A regression coefficient of 0.99 indicates the NiCo 2 O 4 nanomaterial could play a role in the quantification of urea from practical samples. In Table 1 [ 36 , 37 , 38 , 39 , 40 , 41 ], the proposed non-enzymatic urea sensor configuration is found to perform better than or as well as many of the recently published urea sensors/biosensors in terms of wide linear range, especially for the non-enzymatic urea sensors. The LOD of the presented is also superior to many of the reported works’ enzymatic and non-enzymatic sensors, as given in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The obtained Ni(OH) 2 /Mn 3 O 4 /rGO/PANi nanocomposites were used to modify the screen-printed electrodes for the highly sensitive enzyme-less detection of urea. These studies demonstrated that the prepared nanocomposite has the potential to decrease GO functionalities to enhance sensitivity and inhibit the protonation of aniline via graphene structure [68]. Two-dimensional free-standing NiO nanosheets were synthesized using GO paper as a sacrificial template in another study.…”
Section: Graphene and Its Nanocomposites For Noc Sensingmentioning
confidence: 98%
“…In addition, Table 3 compares the electrochemical urea sensor with recently reported nonenzymatic urea sensors. As shown in Table 3, the proposed urea configuration is associated with a wide linear range, a limited detection limit, and simple and scalable synthesis of sensing material [71][72][73][74][75]. Consequently, the presented non-enzymatic urea sensor can be used for detecting urea in a variety of real-life samples as an alternative and efficient method.…”
Section: Investigations Of Urea Non-enzymatic Sensing Parameters Of P...mentioning
confidence: 99%